Green Innovation and Competitive Pressure as Drivers of Sustainable Performance in the Fashion Industry - Isdiana, Firdha Nurul; Sari, Devi Artika; Batu, Kardison Lumban (Research Horizon, 2025)
The fashion industry, particularly the fast fashion segment, significantly contributes to environmental degradation through excessive resource use and waste. This study examines how competitive pressure, green product innovation, and green process innovation influence sustainable firm performance among fashion Micro, Small, and Medium Enterprises (MSMEs) in a region. Using the Natural Resource-Based View (NRBV) as a theoretical framework, the research highlights the strategic role of green innovation in building environmentally valuable, rare, inimitable, and non-substitutable (VRIN) capabilities. A quantitative method was employed, with data collected from 100 MSME actors via a structured questionnaire and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) in AMOS. The findings reveal that competitive pressure, as well as green product and process innovations, have a positive and significant effect on sustainable firm performance. Green product innovation, including eco-friendly materials and circular design, and green process innovation, such as waste-reducing technologies, are identified as crucial strategies for achieving environmental and business goals.